Measurements and calculations of H2-broadening and shift parameters of water vapour transitions of the ν1 + ν2 + ν3band; Molecular Physics; Vol. 116, № 10 - Petrova T. M. Tatjyana Mikhaylovna; Solodov A. M. Aleksandr Mikhaylovich; Solodov A. A. Aleksandr Aleksandrovich; Deichuli V. M. Vladimir Mikhaylovich; Starikov V. I. Vitaly Ivanovich (2017, 2017)
Title screen